Sustainable Conservation and Urban Regeneration The Luxor Example (Research for Development,, 2018)
This book documents research activities and design experimentation carried out within the scope of a project addressing conservation, urban regeneration, responsible use of resources, and sustainable development in a truly exceptional place: the city of Luxor. The project is a collaborative venture between the Politecnico di Milano, the Supreme Council of Antiquities of Egypt, and the Luxor Governorate and is one outcome of a program established by the Egyptian government in 2009 with the goal of discovering a buried treasure, the "Avenue of Sphinxes", which connected the Karnak and Luxor temples in ancient times. Readers will find an account of the excavations themselves, discussion of issues in restoration and conservation, and, above all, archaeological contextualization. Information is provided on integrated solutions to the problems arising from the scale of the excavation, for example in relation to urban morphology, the environment, road systems, infrastructure, housing, tourism, and individual and collective use of spaces. The book will appeal to all with an interest in strategies for enhancement of historical heritage in conjunction with urban regeneration and sustainable development.